Irradiation of the head by 60Co opens the blood-brain barrier for drugs in rats - Bezek, S; Trnovec, T; Scasnár, V; Durisová, M; Kukan, M; Kállay, Z; Laginová, V; Svoboda, V (Experientia, 1990)
The passage of 6 model drugs; acetylsalicylic acid, chloramphenicol, ethimizol, carbisocaine, heptacaine, and diazepam, through the blood-brain barrier, was determined in unirradiated control rats and in animals 1, 3, and 7 days after irradiation of the head only with a dose of 25 Gy from a 60Co source. The brain uptake index (BUI), which compares the uptake of the test substance with that of 3H2O 5 s after their injection into the common carotid artery, was significantly increased in comparison with unirradiated controls 7 days after irradiation, for all substances tested except for ethimizol. For acetylsalicylic acid and chloramphenicol it was also significantly increased in the other time intervals. The less lipophilic substances showed a greater relative increase of BUI than the more lipophilic ones.
Keywords: etimizol; chloramfenikol; mozek; diazepam; Cranial Irradiation; hematoencefalická bariéra; Blood-Brain Barrier; Chloramphenicol; Rats, Inbred Strains; krysa rodu Rattus; zvířata; Regression Analysis; Piperidines; Cobalt Radioisotopes; Male; Diazepam; Brain; Etimizol; Aspirin; Rats; piperidiny; Animals; karbamáty; Carbamates; radioizotopy kobaltu; mužské pohlaví; regresní analýza; kraniální ozáření; inbrední kmeny potkanů